Exploring the landscape of AI in servicescape: a bibliometric review - Airin, Abdul Ghani; Norazidah, Shamsudin; Imaduddin, Abidin; Husna, Hashim; Puteri Fadzline, Muhamad Tamyez (Malaysian Consumer and Family Economics Association, 2024)
This study provides a bibliometric analysis of the expanding landscape of artificial intelligence (AI) within the service sector, utilising data from VOSviewer software. The study utilised a network of bibliographic couplings, where nodes symbolised nations involved in the issue. The analysis was also compared between countries along with its strength of research connections, particularly in the tourism and hospitality field. Key findings have shown that the research community is strong and active, with China, the United States and the United Kingdom playing a significant role in innovating to enhance the service sector using AI. These countries have a robust bibliographic coupling, suggesting a substantial amount of interconnected references and research interests. Gursoy, Kautish, and Ting were recognised as the foremost contributors, and areas of corporate management, social science, and computer science have emerged as significant domains in the research of AI and servicescape. The present study provides a comprehensive bibliometric map that clearly shows various platforms, methods, and technologies that shape the AI trend in servicescape, altering how AI aids servicescape.